A Phase 2b randomized trial of lorecivivint, a novel intra-articular CLK2/DYRK1A inhibitor and Wnt pathway modulator for knee osteoarthritis - Yazici, Y.; McAlindon, T.E.; Gibofsky, A.; Lane, N.E.; Lattermann, C.; Skrepnik, N.; Swearingen, C.J.; Simsek, I.; Ghandehari, H.; DiFrancesco, A.; Gibbs, J.; Tambiah, J.R.S.; et al. (Osteoarthritis and cartilage, 2021)
Lorecivivint (LOR; SM04690), an investigational Wnt pathway modulator, previously demonstrated patient-reported and radiographic outcome improvements vs placebo in clinically relevant subjects with moderate to severe knee osteoarthritis (OA). This study's objective was to identify effective LOR doses. Subjects in this 24-week, Phase 2b, multicenter, randomized, double-blind, placebo (PBO)-controlled trial received an intra-articular injection of 2 mL LOR (0.03, 0.07, 0.15, or 0.23 mg), PBO, or dry-needle sham. The primary efficacy endpoints were changes in Pain NRS [0–10], WOMAC Pain [0–100], WOMAC Function [0–100], and radiographic mJSW outcomes, which were measured using baseline-adjusted analysis of covariance at Week 24. Multiple Comparison Procedure-Modeling (MCP-Mod) was performed for dose modeling. In total, 695/700 subjects were treated. Pain NRS showed significant improvements vs PBO after treatment with 0.07 mg and 0.23 mg LOR at Weeks 12 (−0.96, 95% CI [−1.54, −0.37], P = 0.001; −0.78 [−1.39, −0.17], P = 0.012) and 24 (−0.70 [-1.34, −0.06], P = 0.031; −0.82 [−1.51, −0.12], P = 0.022). Additionally, 0.07 mg LOR significantly improved WOMAC Pain and Function subscores vs PBO at Week 12 (P = 0.04, P = 0.021), and 0.23 mg LOR significantly improved both WOMAC subscores at Week 24 (P = 0.031, P = 0.017). No significant differences from PBO were observed for other doses. No radiographic progression was observed in any group at Week 24. MCP-Mod identified 0.07 mg LOR as the lowest effective dose. This 24-week Phase 2b trial demonstrated the efficacy of LOR on PROs in knee OA subjects. The optimal dose for future studies was identified as 0.07 mg LOR.